The Development of China's Beer Market Since 1990's - Ding, Jingru (My University, 2006)
Background Despite a number of studies placed emphasis on marketing in China, very few studies were conducted to issues regarding to brewing industry in China except routine marketing reports. Aims The primary propose of the present study is attempt to understand how geographic and socio-demographic factors affect China’s brewing industry in terms of distribution of breweries, strategy employment, and consumption pattern. In addition, whether the brewing industry-related phenomenon we observed could be accounted for via existing developed marketing theories, were also examined in this study. Methods In this study, advantages and uncertainties related to the reconstruction of brewing market phenomena in different regions in China, as well as marketing strategies using different information sources, including peer reviewed articles, state statistical registry, marketing relevant magazines, and information that was published on internet, are depicted. Systematic and non-systematic data can be combined in current study using qualitative analysis method. The profiles of breweries’ marketing performances in six China regions were described and comparison was yielded in the light of existing developed marketing theories. Results Market shapes and marketing strategies of China’s brewing industry varied in accordance with different geographic characteristics. Socio-demographic features also affect the picture of China’s brewing market. Brewery ventures preferred to utilise multiple marketing strategies rather than single policy. The existing western market-related theories could not fully account for the phenomena of China’s brewing market. Conclusions The current study compared six regional beer markets in China and interpretation is also made according principles of existing marketing framworks. Owing to the existing western market-related theories could not fully account for the China’s brewing market phenomena. Further theory and model based on Chinese empirical research is eager to be developed.
Keywords: Beer; Brewery Sector; China Market; Marketing Strategy; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|